Pressure-sensitive adhesive composition, pressure-sensitive adhesive sheet and optical film
By using a pressure-sensitive adhesive composition of an acrylate copolymer, a yellowless mutant isocyanate or azoproidine-based crosslinking agent and an organic silicone compound, the adhesiveness and durability of the adhesive in a high temperature and high humidity environment are solved, and the stable bonding and reworkability of the structure under external impact are achieved.
Patent Information
- Application Number
- JP2024538992
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-06-21
- Filing Date
- 2023-01-02
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2043-01-02
AI Technical Summary
Existing pressure-sensitive adhesives or adhesives are difficult to maintain good adhesion and durability under high temperature and high humidity and external physical impact, and cannot effectively prevent structures from being detached or peeled off.
The pressure-sensitive adhesive composition containing an acrylate copolymer, a yellowless variocyanate or azoproidine-based crosslinking agent and an organosilicon compound is used to improve the adhesiveness and reworkability of the adhesive by introducing polar functional groups and controlling the crosslinking degree.
It maintains excellent adhesion and durability under high temperature and high humidity and external impact, prevents structural peeling, and has no residue during heavy industry, which improves the chemical stability and reworkability of the adhesive.
Smart Images

Figure 2025504304000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive composition, a pressure-sensitive adhesive sheet, and an optical film, and more particularly to a pressure-sensitive adhesive composition containing an acrylic copolymer, a pressure-sensitive adhesive sheet produced from the same, and an optical film produced from the pressure-sensitive adhesive sheet. [Background technology]
[0002] For example, adhesives or adhesive sheets can be used to bond display panels of image display devices such as liquid crystal display (LCD) devices and organic light emitting display (OLED) devices to various optical structures or circuit structures, etc. The adhesives must have high adhesive strength as well as improved transparency so as not to deteriorate the optical properties of the image display devices.
[0003] In recent years, displays that have high reliability even under harsh conditions such as high temperature and humidity or under external physical impact have been actively researched. Accordingly, structures to be bonded to the displays must also be formed in a manner that prevents the structures from falling off or peeling off even under harsh conditions or under external impact. Thus, there is a demand for adhesives or adhesive sheets that have high wettability and durability and can bond the display structures.
[0004] For example, Korean Patent Publication No. 2010-0039274 discloses an adhesive for a polarizing plate applied to an image display device. However, conventional known adhesives have limitations in sufficiently securing the above-mentioned properties required for flexible displays. Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a pressure-sensitive adhesive composition capable of forming a pressure-sensitive adhesive layer having improved adhesive properties and reworkability.
[0006] An object of the present invention is to provide a pressure-sensitive adhesive sheet including a pressure-sensitive adhesive layer formed using the pressure-sensitive adhesive composition, and an optical film produced from the pressure-sensitive adhesive sheet. [Means for solving the problem]
[0007] 1. A pressure-sensitive adhesive composition comprising an acrylic copolymer, a non-yellowing type isocyanate- or aziridine-based crosslinking agent, and an organosilicon compound having at least two carbonyl groups.
[0008] 2. The pressure-sensitive adhesive composition according to claim 1, wherein the acrylic copolymer is formed from a polymerizable mixture containing a (meth)acrylate monomer and a (meth)acrylic acid monomer.
[0009] 3. The pressure-sensitive adhesive composition according to item 2, wherein the polymerizable mixture further contains a polar functional group-containing crosslinkable monomer.
[0010] 4. The pressure-sensitive adhesive composition according to item 3, wherein the polar functional group of the polar functional group-containing crosslinkable monomer contains at least one of a hydroxy group, an amide group, and an amine group.
[0011] 5. The pressure-sensitive adhesive composition according to the above item 3, wherein the content of the polar functional group-containing crosslinkable monomer is 0.1% by weight to 5% by weight based on the total weight of the polymerizable mixture.
[0012] 6. The pressure-sensitive adhesive composition according to item 2 above, wherein the (meth)acrylate monomer comprises a first monomer which is an alkyl (meth)acrylate monomer having 1 to 3 carbon atoms, and a second monomer which is an alkyl (meth)acrylate monomer having 4 to 12 carbon atoms.
[0013] 7. The pressure-sensitive adhesive composition according to item 6, wherein the content of the first monomer is 10% by weight to 40% by weight based on the total weight of the polymerizable mixture.
[0014] 8. The pressure-sensitive adhesive composition according to the above item 2, wherein the content of the (meth)acrylic acid monomer is 0.01% by weight to 1% by weight based on the total weight of the polymerizable mixture.
[0015] 9. The pressure-sensitive adhesive composition according to item 1, wherein the organosilicon compound contains a nitrogen atom or a sulfur atom.
[0016] 10. The pressure-sensitive adhesive composition according to item 9, wherein the organosilicon compound contains an amine group or a sulfide group.
[0017] 11. The pressure-sensitive adhesive composition according to claim 1, wherein the organosilicon compound has two carbonyl groups linked by a methylene group.
[0018] 12. The pressure-sensitive adhesive composition according to item 11, wherein the organosilicon compound has a malonyl group or an acetoacetyl group.
[0019] 13. The pressure-sensitive adhesive composition according to item 1 above, wherein the organosilicon compound comprises a compound represented by the following chemical formula 1 or the following chemical formula 2:
[0020] [ka] [ka] (R 1 is an alkoxy group having 1 to 12 carbon atoms, and R 6 is an alkyl group having 1 to 12 carbon atoms or an alkoxy group having 1 to 12 carbon atoms, R 2 and R 7 are each independently a divalent aliphatic hydrocarbon having 1 to 30 carbon atoms, R 3 ~R 5 and R 8 ~R 10 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an alkenyl group having 2 to 12 carbon atoms, an alkynyl group having 2 to 12 carbon atoms, or an alkoxy group having 1 to 12 carbon atoms.
[0021] 14. A pressure-sensitive adhesive composition as described in item 1, comprising 100 parts by weight of the acrylic copolymer, 0.1 to 3 parts by weight of the non-yellowing type isocyanate-based or aziridine-based crosslinking agent, and 0.01 to 3 parts by weight of the organosilicon compound.
[0022] 15. The pressure-sensitive adhesive composition according to claim 1, further comprising an ionic antistatic agent.
[0023] 16. A pressure-sensitive adhesive sheet comprising a base film and an adhesive layer disposed on the base film and formed using the pressure-sensitive adhesive composition according to item 1.
[0024] 17. The pressure-sensitive adhesive sheet according to item 16, wherein the pressure-sensitive adhesive sheet has an adhesive strength change rate according to the following formula 2 of 0.8 to 2.2: [Formula 2] Adhesive strength change rate = P H / P C (In formula 2, P C is the adhesive strength measured by attaching the adhesive sheet to an object, leaving it for 24 hours under conditions of a temperature of 23° C. and a relative humidity of 50%, and then peeling the adhesive sheet from the object at a peel speed of 300 mm / min and a peel angle of 180°; P H is the adhesive strength measured by attaching the pressure-sensitive adhesive sheet to the object, leaving it for 48 hours under conditions of a temperature of 50°C and a relative humidity of 50%, and then peeling the pressure-sensitive adhesive sheet from the object at a peeling speed of 300 mm / min and a peeling angle of 180° under conditions of a temperature of 23°C and a relative humidity of 50%.
[0025] 18. An optical film comprising: a substrate film; an adhesive layer disposed on an upper surface of the substrate film and formed using the adhesive composition according to item 1; and an antireflection layer disposed on a lower surface of the substrate film.
[0026] 19. An image display device comprising the optical film according to item 18. Effect of the Invention
[0027] The pressure-sensitive adhesive composition according to the exemplary embodiment can include an acrylic copolymer, an organosilicon compound having at least two carbonyl groups, and a non-yellowing type isocyanate-based or aziridine-based crosslinking agent, which can improve the chemical stability and reworkability of the pressure-sensitive adhesive composition. [Brief description of the drawings]
[0028] [Figure 1] FIG. 2 is a schematic cross-sectional view illustrating a pressure-sensitive adhesive sheet according to an exemplary embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view illustrating a pressure-sensitive adhesive sheet according to an exemplary embodiment. [Diagram 3] 1 is a schematic cross-sectional view illustrating an optical film according to an exemplary embodiment. [Figure 4] 1 is a schematic cross-sectional view for explaining an image display device according to an exemplary embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The present invention provides a pressure-sensitive adhesive composition including an acrylic copolymer, a non-yellowing type isocyanate-based or aziridine-based crosslinker, and an organosilicon compound having at least two carbonyl groups. Also provided are a pressure-sensitive adhesive sheet and an optical film including a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition.
[0030] The present invention will be described in detail below.
[0031] <Adhesive composition> The pressure-sensitive adhesive composition according to the exemplary embodiment may include an acrylic copolymer. The acrylic copolymer may include a copolymer formed from a polymerizable mixture including a (meth)acrylate monomer and (meth)acrylic acid. The term "(meth)acrylate" used in this application is intended to encompass acrylate or methacrylate. The term "(meth)acrylic acid" used in this application is intended to encompass acrylic acid or methacrylic acid.
[0032] The (meth)acrylate monomer may include a first monomer of an alkyl (meth)acrylate having 1 to 3 carbon atoms, and a second monomer of an alkyl (meth)acrylate having 4 to 12 carbon atoms.
[0033] The first monomer and the second monomer may be a compound derived from an aliphatic alcohol having 1 to 12 carbon atoms.
[0034] Examples of the first monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, etc., and preferably methyl (meth)acrylate. These may be used alone or in combination of two or more.
[0035] In some embodiments, the content of the first monomer may be 10% by weight to 40% by weight, preferably 15% by weight to 35% by weight, based on the total weight of the polymerizable mixture. If the content of the first monomer is less than 10% by weight, sufficient adhesive strength may not be achieved. If the content of the first monomer is more than 40% by weight, the adhesive strength may increase too much, resulting in reduced reworkability.
[0036] Examples of the second monomer include n-butyl (meth)acrylate, 2-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, etc. The second monomer may be preferably n-butyl (meth)acrylate or 2-ethylhexyl (meth)acrylate. These may be used alone or in combination of two or more.
[0037] In some embodiments, the content of the second monomer may be 60% by weight to 89% by weight, preferably 65% by weight to 80% by weight, based on the total weight of the polymerizable mixture. If the content of the first monomer is less than 60% by weight, sufficient adhesive strength may not be achieved. Within this range, it is possible to prevent a decrease in the cohesive strength of the adhesive composition, which would otherwise cause a decrease in the durability of the adhesive layer, and to improve the crosslink density and adhesive strength of the adhesive layer.
[0038] According to an exemplary embodiment, the polymerizable mixture includes both the first monomer and the second monomer, and can achieve improved adhesion while preventing damage to the substrate and residual adhesive material during rework.
[0039] The (meth)acrylic acid monomer can impart adhesive strength to the pressure-sensitive adhesive composition. For example, the acrylic copolymer has an acidic group derived from the (meth)acrylic acid monomer, which can improve the adhesion and crosslinking degree of the pressure-sensitive adhesive composition.
[0040] However, as the content of the (meth)acrylic acid monomer increases, the hydrophilicity of the adhesive composition may increase, and the surface migration of an ionic antistatic agent described below may deteriorate. In addition, the cohesive strength and adhesion of the adhesive layer may decrease as the crosslinking agent described below reacts with the acidic group derived from the (meth)acrylic acid and is consumed.
[0041] In some embodiments, the content of the (meth)acrylic acid may be 1 wt% or less based on the total weight of the polymerizable mixture. For example, the content of the (meth)acrylic acid monomer may be 0.01 wt% to 1 wt%, preferably 0.05 wt% to 1 wt%, more preferably 0.05 wt% to 0.5 wt% based on the total weight of the polymerizable mixture. If the content of the (meth)acrylic acid monomer is less than 0.01 wt%, the adhesive strength of the adhesive composition may decrease. If the content of the (meth)acrylic acid monomer is more than 1 wt%, the adhesive strength may increase too much, causing a decrease in reworkability, which may affect the surface migration of the ionic antistatic agent and reduce durability.
[0042] According to an exemplary embodiment, the polymerizable mixture may further include a polar functional group-containing crosslinkable monomer. For example, the acrylic copolymer may include a copolymer formed from a polymerizable mixture including a (meth)acrylate monomer, (meth)acrylic acid, and a crosslinkable monomer having a polar functional group.
[0043] The polar functional group-containing crosslinkable monomer can improve the degree of crosslinking of the acrylic copolymer, and can also react with the non-yellowing isocyanate- or aziridine-based crosslinking agent described below to prevent the cohesive force of the adhesive layer from being destroyed under high temperature and high humidity conditions, thereby imparting adhesive strength.
[0044] The crosslinkable monomer may include a hydroxy group, an amide group, an amine group, etc., as a polar functional group. In some embodiments, the crosslinkable monomer may include a hydroxy group-containing monomer, an amide group-containing monomer, and / or an amine group-containing monomer. These may be used alone or in combination of two or more.
[0045] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 2-hydroxyethylene glycol (meth)acrylate, 2-hydroxypropylene glycol (meth)acrylate, hydroxyalkylene glycol (meth)acrylate having an alkylene group with 2 to 4 carbon atoms, 4-hydroxybutyl vinyl ether, 5-hydroxypentyl vinyl ether, 6-hydroxyhexyl vinyl ether, 7-hydroxyheptyl vinyl ether, 8-hydroxyoctyl vinyl ether, 9-hydroxynonyl vinyl ether, and 10-hydroxydecyl vinyl ether. These may be used alone or in combination of two or more.
[0046] Examples of the amide group-containing monomer include (meth)acrylamide, N-isopropylacrylamide, N-tert-butylacrylamide, 3-hydroxypropyl(meth)acrylamide, 4-hydroxybutyl(meth)acrylamide, 6-hydroxyhexyl(meth)acrylamide, 8-hydroxyoctyl(meth)acrylamide, 2-hydroxyethylhexyl(meth)acrylamide, etc. These may be used alone or in combination of two or more.
[0047] The amine group-containing monomer may include a tertiary amine group-containing monomer. Examples of the tertiary amine group-containing monomer include N,N-(dimethylamino)ethyl (meth)acrylate, N,N-(diethylamino)ethyl (meth)acrylate, and N,N-(dimethylamino)propyl (meth)acrylate. These may be used alone or in combination of two or more.
[0048] Preferably, the crosslinkable monomer may include 4-hydroxybutyl vinyl ether and / or (meth)acrylamide.
[0049] In some embodiments, the content of the crosslinkable monomer having a polar functional group may be 0.05% by weight to 5% by weight, preferably 0.1% by weight to 3% by weight, based on the total weight of the polymerizable mixture. If the content of the crosslinkable monomer is less than 0.05% by weight, the cohesive strength of the pressure-sensitive adhesive composition may be reduced, resulting in reduced durability. If the content of the crosslinkable monomer is more than 5% by weight, the gel fraction of the pressure-sensitive adhesive composition may be too high, resulting in reduced adhesive strength and durability.
[0050] In some embodiments, in addition to the above monomers, other polymerizable monomers known in the art may be further included in a range that does not reduce the adhesive strength, for example, 10 wt % or less based on the total weight of the polymerizable mixture.
[0051] The method for producing the acrylic copolymer is not particularly limited, and the copolymer may be produced by a method commonly used in the art, such as bulk polymerization, solution polymerization, emulsion polymerization, or suspension polymerization, and preferably by a solution polymerization method. In addition, a solvent, a polymerization initiator, a chain transfer agent for controlling molecular weight, and the like, which are commonly used in polymerization, may be used.
[0052] In some embodiments, the weight average molecular weight (polystyrene equivalent, Mw) of the acrylic copolymer may be 50,000 to 2,000,000, preferably 400,000 to 2,000,000. For example, the weight average molecular weight can be measured by gel permeation chromatography (GPC). If the weight average molecular weight of the acrylic copolymer is less than 50,000, the cohesive force between the copolymers may be insufficient, resulting in reduced adhesion durability. If it exceeds 2,000,000, a large amount of dilution solvent may be required to ensure processability during coating.
[0053] The non-yellowing type isocyanate-based or aziridine-based crosslinking agent can improve the cohesive strength, adhesion and high temperature reliability of the adhesive, and can play a role in maintaining the shape of the adhesive.
[0054] The yellowing type isocyanate crosslinking agent may refer to a compound in which a phenyl carbon is directly bonded to a nitrogen atom of an isocyanate among isocyanate crosslinking agents, and the non-yellowing type isocyanate crosslinking agent may refer to the remainder of the above isocyanate crosslinking agents excluding the above yellowing type isocyanate crosslinking agents.
[0055] Non-yellowing type isocyanate-based compounds and aziridine-based compounds have high reactivity with polar functional groups and can have improved adhesion to corona discharge-treated or plasma-treated substrate films.
[0056] Examples of the isocyanate compound include diisocyanate compounds such as xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, and tetramethyl xylylene diisocyanate; an adduct obtained by reacting 1 equivalent of a polyhydric alcohol compound such as trimethylolpropane with 3 equivalents of a diisocyanate compound; an isocyanurate obtained by self-condensing 3 equivalents of a diisocyanate compound; a biuret obtained by condensing 1 equivalent of diisocyanate with diisocyanate urea obtained from 2 equivalents of the 3 equivalents of a diisocyanate compound; and polyfunctional isocyanate compounds containing three functional groups such as triphenylmethane triisocyanate and methylene bis triisocyanate. These compounds may be used alone or in combination of two or more.
[0057] Examples of the aziridine-based compound include pentaerythritol-tris-(β-(N-aziridinyl)propionate, trimethylolpropane-tris(β-N-aziridinyl)propionate, trimethylolpropane tris(2-methyl-1-aziridinepropionate), N,N'-toluene-2,4-bis(1-aziridinecarboxamide), N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), triethylenemelamine, bisisoprolol-1-(2-methylaziridine), and tri-1-aziridinylphosphine oxide. These may be used alone or in combination of two or more.
[0058] In some embodiments, the content of the crosslinking agent may be 0.1 to 3 parts by weight, preferably 0.1 to 2 parts by weight, based on 100 parts by weight of the acrylic copolymer. If the content of the crosslinking agent is less than 0.1 parts by weight, the cohesive force may be reduced due to insufficient crosslinking degree, and the adhesive durability and cuttability may be reduced. If the content of the crosslinking agent is more than 3 parts by weight, the crosslinking reaction may occur too much, causing an increase in residual stress, and the adhesion to the adhesion target may be reduced.
[0059] The pressure-sensitive adhesive composition according to the exemplary embodiment can include an organosilicon compound having at least two carbonyl groups. In one embodiment, the organosilicon compound can include two carbonyl groups linked by a methylene group. Therefore, the organosilicon compound can increase the adhesive strength of the pressure-sensitive adhesive composition, and can suppress the generation of bubbles, lifting, and breakage of the adhesive layer.
[0060] In some embodiments, the organosilicon compound may include a malonyl group or an acetoacetyl group, which may further improve the adhesiveness of the pressure-sensitive adhesive composition, and may improve the heat resistance and moist heat resistance.
[0061] In some embodiments, the organosilicon compound can have nitrogen or sulfur atom.For example, the organosilicon compound can include amine or sulfide group.The organosilicon compound has amine or sulfide group together with malonyl or acetoacetyl group, so that it can realize improved reworkability even after being left for a long time under heat-resistant and moist heat-resistant conditions, and can improve adhesion durability and adhesion reliability.
[0062] In some embodiments, the organosilicon compound can include a compound represented by Formula 1 or Formula 2:
[0063] [ka] [ka]
[0064] R 1 may be an alkoxy group having 1 to 12 carbon atoms. 1 Examples of the group include a methoxy group, an ethoxy group, and an isopropyloxy group. From the viewpoint of reworkability, a methoxy group may be preferable.
[0065] R 6 may be an alkyl group having 1 to 12 carbon atoms or an alkoxy group having 1 to 12 carbon atoms. 6 Examples of the group include a methyl group, an ethyl group, an isopropyl group, a methoxy group, an ethoxy group, and an isopropyloxy group. From the viewpoint of reworkability, the group may be preferably a methyl group or a methoxy group.
[0066] R 2 and R 7 may each independently be a divalent aliphatic hydrocarbon group having 1 to 30 carbon atoms. For example, R 2 and R 7may be an alkylene group having 1 to 30 carbon atoms, an alkenylene group having 2 to 30 carbon atoms, or an alkynylene group having 2 to 30 carbon atoms.
[0067] R 3 ~R 5 and R 8 ~R 10 may each independently be a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an alkenyl group having 2 to 12 carbon atoms, an alkynyl group having 2 to 12 carbon atoms, or an alkoxy group having 1 to 12 carbon atoms. 3 ~R 5 At least one of, and R 8 ~R 10 At least one of these is preferably an alkoxy group having 1 to 12 carbon atoms, and the number of carbon atoms can be adjusted in consideration of the relationship between adhesive strength and reworkability.
[0068] In some embodiments, the content of the organosilicon compound may be 0.01 to 3 parts by weight, preferably 0.1 to 2 parts by weight, and more preferably 0.1 to 1 part by weight, based on 100 parts by weight of the acrylic copolymer. Within this range, the durability and adhesion of the adhesive layer formed from the adhesive composition can be improved.
[0069] In some embodiments, the pressure-sensitive adhesive composition may further include an ionic antistatic agent. The ionic antistatic agent may include an ionic salt composed of an anion and a cation, and may impart ionic conductivity to the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition. For example, the surface resistivity of the pressure-sensitive adhesive layer may be 10×10 10 It may be Ω / □ or less, and preferably 7×10 10 It may be Ω / □ or less.
[0070] In some embodiments, the ionic antistatic agent can include an alkali metal salt, an ionic liquid, or an ionic solid, preferably an ionic solid.
[0071] By including an ionic solid as an ionic antistatic agent, the stability of the pressure-sensitive adhesive composition over time and the durability of the pressure-sensitive adhesive layer can be improved. In addition, the ionic solid has high compatibility with the other components described above, and can maintain high transparency of the pressure-sensitive adhesive composition.
[0072] In some embodiments, the melting point of the ionic solid may be 20° C. or higher, specifically 20° C. to 50° C. In this case, the mobility of the ionic solid is minimized, and the durability and reliability of the pressure-sensitive adhesive sheet or optical film can be improved. For example, if the melting point of the ionic solid is less than 20° C., the mobility of the ionic solid increases, and the ionic solid may move to the edge of the pressure-sensitive adhesive sheet or optical film and dissolve.
[0073] In some embodiments, the ionic solid contains Cl as the anion. - , Br - , I - , AlCl 4 - , Al 2 Cl 7 - , B.F. 4 - , P.F. 6 - , ClO 4 - , NO 3 - , CO 3 2- , C.H. 3 COO - , C.F. 3 COO - , C.H. 3 SO 3 - , C.F. 3 SO 3 - , (FSO 2 ) 2 N - , (CF 3 SO 2 ) 2 N - , (CF 3 SO 2 ) 3 C -, AsF 6 - , SbF 6 - , NbF 6 - , TaF 6 - , F(HF) n - , (CN) 2 N - , C 4 F 9 SO 3 - , (C 2 F 5 SO 2 ) 2 N - , C 3 F 7 COO - , C 6 H 5 COO - , (CF 3 SO 2 )(CF 3 CO)N - , OTF - (trifluoromethanesulfonate), OTs - (toluenesulfonate), OMs - (methanesulfonate), and / or BPh 4 - (tetraphenylborate) and the like.
[0074] In some embodiments, the ionic solid can include as a cation imidazolium, pyridinium, alkylammonium, alkylpyrrolidinium, and / or alkylphosphonium.
[0075] In some embodiments, the content of the ionic antistatic agent may be 0.01 to 5 parts by weight based on 100 parts by weight of the acrylic copolymer. Within this range, the antistatic properties of the adhesive layer are improved, and the durability of the adhesive layer can be maintained at an excellent level.
[0076] The pressure-sensitive adhesive composition may further include additives known in the art to adjust adhesive strength, cohesive strength, viscosity, elastic modulus, glass transition temperature, etc., as required depending on the application. For example, the pressure-sensitive adhesive composition may include additives such as tackifiers, antioxidants, corrosion inhibitors, leveling agents, surface lubricants, dyes, pigments, defoamers, fillers, light stabilizers, plasticizers, etc.
[0077] <Adhesive sheet> Hereinafter, the embodiments of the present invention will be described in more detail with reference to the drawings. However, the drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and, together with the detailed description of the invention, serve to aid in further understanding of the technical concept of the present invention, and therefore the present invention should not be interpreted as being limited only to the matters depicted in the drawings.
[0078] FIG. 1 is a schematic cross-sectional view showing a pressure-sensitive adhesive sheet according to an exemplary embodiment.
[0079] Referring to FIG. 1 , an adhesive sheet according to an exemplary embodiment may include a base film 110, an adhesive layer 120 disposed on the upper surface of the base film 110, and a release film 130 disposed on the upper surface of the adhesive layer 120.
[0080] The adhesive layer can be formed from the above-mentioned adhesive composition. For example, the adhesive layer 120 can be formed by applying an adhesive composition containing an acrylic copolymer, a non-yellowing type isocyanate-based or aziridine-based crosslinking agent, and an organosilicon compound having at least two carbonyl groups onto the substrate film 110 and curing the composition.
[0081] In some embodiments, the base film 110 may include an acrylic resin, a cellulose resin, a polyolefin resin, a polyester resin, etc. In this case, the transparency, mechanical strength, thermal stability, moisture barrier property, isotropy, etc. of the base film 110 may be improved.
[0082] For example, the base film 110 may include acrylic resins such as polymethyl (meth)acrylate and polyethyl (meth)acrylate; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene isophthalate, polyethylene naphthalate and polybutylene naphthalate; cellulose resins such as diacetyl cellulose, triacetyl cellulose and cellulose acetate butylene; polyolefin resins such as polyethylene, polypropylene, cycloolefin, polyolefin having a norbornene structure and ethylene-propylene copolymer; sulfone resins; polyether ether ketone resins; arylate resins; or mixtures of the above resins.
[0083] In one embodiment, at least one surface of the base film 110, for example, the surface on which the adhesive layer 120 is formed, can be surface-treated. For example, one surface of the base film 110 can be subjected to corona discharge treatment, plasma treatment, blast treatment, primer treatment, or the like.
[0084] The surface treatment can generate a carboxylic acid derivative (R-COOH) on the surface of the base film 110. The carboxyl group of the carboxylic acid derivative can react with the pressure-sensitive adhesive composition, thereby further improving the adhesion of the pressure-sensitive adhesive layer to the base film.
[0085] In one embodiment, the surface of the substrate film 110 may not be saponified. The substrate film used in the adhesive sheet has a hydrophobic surface, which may deteriorate the adhesion and adhesive strength to the adhesive. In this case, the adhesion between the substrate and the adhesive can be improved by performing a pretreatment process in which the surface of the substrate film is immersed in an alkaline aqueous solution to saponify it, forming another coating layer between the substrate and the adhesive, or subjecting the surface of the substrate film to a corona or plasma treatment.
[0086] However, when a saponification process is performed or a separate coating layer is formed, the process becomes complicated, which may reduce the yield and processability of the adhesive sheet, and the additional pretreatment or coating layer formation process may cause contamination and deterioration of the quality of the adhesive sheet.
[0087] In the adhesive composition according to the above embodiment, the organosilicon compound having a malonyl group or an acetoacetyl group enhances the affinity between the surface of the base film 110 and the adhesive composition, thereby improving the adhesion of the adhesive layer 120 to the surface of the base film 110. In addition, the adhesive composition can maintain heat resistance, moisture and heat resistance, durability, and adhesive reliability under harsh conditions of high temperature and high humidity, and can achieve improved reworkability even after being left for a long time under the harsh conditions.
[0088] The adhesive layer 120 can be formed by applying the above-mentioned adhesive composition onto at least one surface of the base film 110, and drying and / or curing the composition. For example, the adhesive layer 120 can be formed by applying the adhesive composition onto the base film 110 by a coating method such as roll coating, gravure coating, reverse coating, spray coating, air knife coating, or die coating.
[0089] According to an exemplary embodiment, the gel fraction of the adhesive layer 120 may be 60% to 80%, and preferably 65% to 75%. The gel fraction of the adhesive layer 120 can be calculated by the following Equation 1.
[0090] [Formula 1] Gel fraction (%) = W2 / W1 × 100
[0091] In the formula 1, W1 may be the initial weight of the adhesive layer, and W2 may be the weight measured after the adhesive layer is immersed in an ethyl acetate solution at room temperature for 3 days and dried at 120°C for 24 hours.
[0092] If the gel fraction of the adhesive layer 120 is less than 60%, the degree of cross-linking and cohesive strength will be low, which may result in reduced durability over time and reduced reworkability. If the gel fraction of the adhesive layer 120 is more than 80%, the durability and adhesion of the adhesive layer 120 may be reduced due to excessive cross-linking, which may cause damage to the target object when the adhesive sheet is peeled off.
[0093] According to an exemplary embodiment, the adhesive sheet may have an adhesive strength change rate of 0.8 to 2.2, preferably 1.1 to 2.1, according to the following formula 2. Within this range, adhesive reliability at room temperature and high temperature can be ensured, and improved reworkability can be achieved.
[0094] [Formula 2] Adhesive strength change rate = P H / P C
[0095] In formula 2, P C can indicate the adhesive strength measured by leaving an adhesive sheet attached to an object to be adhered under conditions of a temperature of 23°C and a relative humidity of 50% for 24 hours, and then peeling the adhesive sheet from the object to be adhered under the above conditions at a peel speed of 300 mm / min and a peel angle of 180°.
[0096] P H can indicate the adhesive strength measured by leaving an adhesive sheet attached to an object to be adhered under conditions of a temperature of 50°C and a relative humidity of 50% for 48 hours, and then peeling the adhesive sheet from the object to be adhered under conditions of a temperature of 23°C and a relative humidity of 50% at a peel speed of 300 mm / min and a peel angle of 180°.
[0097] The rate of change in adhesive strength indicates the ratio of adhesive strength at room temperature (about 23°C) to adhesive strength at elevated temperature (about 50°C), and can be used as a measure for judging reworkability after being left at elevated temperature for a long period of time.
[0098] 1, the adhesive sheet may further include a release film 130 disposed on one side of the adhesive layer 120. For example, the adhesive sheet may include a base film 110, an adhesive layer 120, and a release film 130 disposed in that order.
[0099] In some embodiments, the adhesive sheet may be provided in a form in which a base film 110 and a release film 130 are attached to both sides. Referring to Fig. 2, when using the adhesive sheet, the release film 130 may be removed from the adhesive sheet. In this case, the release film 130 may be removed from the adhesive sheet, and the exposed adhesive layer 120 may be attached to an object to be adhered (e.g., a display panel).
[0100] In some embodiments, the adhesive sheet may be provided in a form in which release films 130 are attached to both sides of the adhesive layer 120 .
[0101] For example, the release film 130 attached to one side of the adhesive sheet can be removed, and the optical substrate film 110 or a functional layer (e.g., an anti-reflection layer) can be attached to the exposed surface of the adhesive layer 120 to form a laminate.
[0102] In one embodiment, the anti-reflective layer may be provided as an anti-reflective plate attached to one side of the optical substrate film 110, or may be attached onto the other side of the optical substrate film 110 to which the adhesive layer 120 of the adhesive sheet is attached.
[0103] <Optical films, image display devices> FIG. 3 is a schematic cross-sectional view illustrating an optical film according to an exemplary embodiment.
[0104] Referring to FIG. 3, the optical film may include a base film 110, an adhesive layer 120 disposed on one side of the base film 110, and an optical functional layer 140 disposed on the other side of the base film 110.
[0105] For example, the optical film can be produced by forming an optical functional layer 140 on one side of a base film 110, and then applying and curing an adhesive composition on the other side of the base film 110 to form an adhesive layer 120.
[0106] In some embodiments, the optical functional layer 140 can include an anti-reflection layer, a hard coat layer, a retardation layer, a polarizer, etc. For example, the optical film can be provided as an anti-reflection film, a hard coat film, a window film, a retardation film, a polarizer, etc., depending on the optical functional layer 140.
[0107] In some embodiments, the optical film may further include a release film disposed on one side of the adhesive layer 120. For example, the optical film may be provided in a form in which the base film 110 and the release film are attached to both sides of the adhesive layer 120. In this case, the release film formed on one side of the adhesive layer 120 may be removed, and the exposed surface of the adhesive layer 120 may be attached to a target object (e.g., a display panel).
[0108] In some embodiments, when the release film 130 is attached to both sides of the adhesive layer 120, the release film 130 on one side of the adhesive layer 120 can be removed, and the optical function layer 140 can be attached to the exposed surface. Also, the release film 130 remaining on the other side of the adhesive layer 120 can be additionally removed, and an object (e.g., a display panel) can be attached to the exposed surface.
[0109] FIG. 4 is a schematic cross-sectional view for explaining an image display device according to an exemplary embodiment.
[0110] According to an exemplary embodiment, the image display device may include a display panel 200 and an optical film disposed on the display panel 200 .
[0111] In some embodiments, the image display device may include a display panel 200 and an optical film disposed on the upper surface of the display panel via an adhesive layer 120. For example, the release film may be removed from the optical film, and the exposed adhesive layer 120 may be attached to the display panel 200 to provide the image display device.
[0112] The display panel 200 may be a liquid crystal display panel (LCD), an organic light emitting display panel (OLED), or a quantum dot light emitting display panel (QLED).
[0113] In addition to the above components, the image display device may further include other components known in the art, such as a retardation film, a hard coat film, a protective film, a window film, a touch panel, etc. The above components may be attached to each other by the adhesive composition according to the exemplary embodiment.
[0114] As described above, improved adhesion and bonding between the base film 110 and the adhesive layer 120 can provide improved durability and stability. Therefore, even when subjected to physical external forces such as repeated bending or under harsh conditions such as high temperature and high humidity, the adhesive reliability of the image display device can be maintained for a long period of time, and breakage, peeling, and lifting of each component can be prevented.
[0115] In addition, even after long periods of exposure to harsh conditions such as high temperature and humidity, the adhesive sheet can be peeled off without damaging the target object during rework or leaving any adhesive residue.
[0116] Below, preferred embodiments are presented to aid in understanding the present invention. However, these embodiments are merely illustrative of the present invention and do not limit the scope of the appended claims. It will be apparent to those skilled in the art that various changes and modifications to the embodiments are possible within the scope of the scope and technical spirit of the present invention, and it is natural that such changes and modifications fall within the scope of the appended claims.
[0117] Manufacturing Example Production Example 1: Production of acrylic copolymer (A-1) In a 1L reactor in which nitrogen gas was refluxed and a cooling device was installed for easy temperature control, 100 parts by weight of a monomer mixture consisting of 68.8% by weight of n-butyl acrylate (BA), 30% by weight of methacrylate (MA), 0.2% by weight of acrylic acid (AA), and 1.0% by weight of 2-hydroxyethyl methacrylate (2-HEMA) was added, followed by 100 parts by weight of ethyl acetate (EA) as a solvent. After that, nitrogen gas was added for 1 hour to remove oxygen, and the temperature was maintained at 62°C. After the mixture was mixed uniformly, 0.07 parts by weight of azobisisobutyronitrile (AIBN) was added as a reaction initiator and reacted for 8 hours to produce an acrylic copolymer (A-1) with a molecular weight of about 1.24 million.
[0118] Production Example 2: Production of acrylic copolymer (A-2) An acrylic copolymer (A-2) having a molecular weight of about 1.27 million was produced in the same manner as in Production Example 1, except that a monomer mixture consisting of 78.8 wt% n-butyl acrylate (BA), 20 wt% methacrylate (MA), 0.2 wt% acrylic acid (AA), and 1.0 wt% 2-hydroxyethyl methacrylate (2-HEMA) was added.
[0119] Production Example 3: Production of acrylic copolymer (A-3) An acrylic copolymer (A-3) having a molecular weight of about 1.42 million was produced in the same manner as in Production Example 1, except that a monomer mixture consisting of 74 wt% n-butyl acrylate (BA), 25 wt% methacrylate (MA), 0.3 wt% acrylic acid (AA), and 0.7 wt% 2-hydroxyethyl methacrylate (2-HEMA) was added.
[0120] Production Example 4: Production of acrylic copolymer (A-4) An acrylic copolymer (A-4) having a molecular weight of about 1.4 million was produced in the same manner as in Production Example 1, except that a monomer mixture consisting of 53.3 wt% n-butyl acrylate (BA), 45 wt% methacrylate (MA), 0.2 wt% acrylic acid (AA), and 1.5 wt% 2-hydroxyethyl methacrylate (2-HEMA) was added.
[0121] Production Example 5: Production of acrylic copolymer (A-5) An acrylic copolymer (A-5) having a molecular weight of about 1.41 million was produced in the same manner as in Production Example 1, except that a monomer mixture consisting of 93.8 wt% n-butyl acrylate (BA), 5 wt% methacrylate (MA), 0.2 wt% acrylic acid (AA), and 1.0 wt% 2-hydroxyethyl methacrylate (2-HEMA) was added.
[0122] Production Example 6: Production of acrylic copolymer (A-6) An acrylic copolymer (A-6) having a molecular weight of about 1.39 million was produced in the same manner as in Production Example 1, except that a monomer mixture consisting of 67.8 wt% n-butyl acrylate (BA), 30 wt% methacrylate (MA), 1.2 wt% acrylic acid (AA), and 1.0 wt% 2-hydroxyethyl methacrylate (2-HEMA) was added.
[0123] Production Example 7: Production of acrylic copolymer (A-7) An acrylic copolymer (A-7) having a molecular weight of about 1.4 million was produced in the same manner as in Production Example 1, except that a monomer mixture consisting of 69 wt% n-butyl acrylate (BA), 30 wt% methacrylate (MA), and 1.0 wt% 2-hydroxyethyl methacrylate (2-HEMA) was added.
[0124] Working Example (1) Production of adhesive composition The components and contents shown in Table 1 below were mixed and then diluted with ethyl acetate to a solid content of 20% by weight to prepare pressure-sensitive adhesive compositions of Examples and Comparative Examples. The contents are in parts by weight.
[0125] (2) Manufacturing of adhesive sheets The prepared adhesive composition was applied onto a release film coated with a silicone release agent and dried at 100° C. for 2 minutes to form an adhesive layer with a thickness of 20 μm. A corona discharge-treated triacetyl cellulose (TAC) film was laminated onto the formed adhesive layer to prepare an adhesive sheet.
[0126] [Table 1] JPEG2025504304000007.jpg55150
[0127] The specific component names shown in Table 1 are as follows. Acrylic copolymer (A) A-1: Copolymer prepared in Preparation Example 1 A-2: Copolymer prepared in Preparation Example 2 A-3: Copolymer prepared in Preparation Example 3 A-4: Copolymer prepared in Preparation Example 4 A-5: Copolymer prepared in Preparation Example 5 A-6: Copolymer prepared in Preparation Example 6 A-7: Copolymer prepared in Preparation Example 7 Crosslinking agent (B) B-1:D-110N (manufactured by Mitsui Chemicals) B-2: Coronate-HXR (manufactured by Nippon Polyurethane Industry Co., Ltd.) B-3: CL-467 (manufactured by MENADIONA) B-4: Coronate-L (Nippon Polyurethane Industry Co., Ltd.) Organosilicon Compounds (C) C-1: A compound represented by the following chemical formula 1-1 [ka] C-2: A compound represented by the following chemical formula 2-1 [ka] C-3: A compound represented by the following chemical formula 3 [ka] Antistatic Agent (D) 1-Octyl-4-methylpyridinium hexafluorophosphate
[0128] Experimental Example (1) Evaluation of adhesive strength The adhesive sheet produced above was cut to a length of 25 mm x width of 100 mm, and the release film was peeled off. The exposed adhesive layer was then attached to a glass substrate (#1737, Corning Incorporated) at a pressure of 0.25 MPa, and autoclaved at a temperature of 50°C and a pressure of 5 atm for 20 minutes to prepare a test specimen.
[0129] To measure the room temperature adhesive strength, the test piece prepared above was left for 24 hours under conditions of 23°C temperature and 50% RH. Using a universal tensile tester (UTM, manufactured by Instron), the adhesive sheet was peeled from the glass substrate at a peeling speed of 300 mm / min and a peeling angle of 180° to measure the room temperature adhesive strength.
[0130] To measure the heated adhesive strength, the test piece prepared above was left for 48 hours under conditions of a temperature of 50°C and 50% RH. Then, the heated adhesive strength was measured by peeling the adhesive sheet from the glass substrate at a peeling speed of 300 mm / min and a peeling angle of 180° using a universal tensile tester (UTM, manufactured by Instron) under conditions of a temperature of 23°C and 50% RH.
[0131] (2) Measurement of reworkability The adhesive sheet produced above was cut to a length of 25 mm x width of 100 mm, and the release film was peeled off. The exposed adhesive layer was then attached to a glass substrate at a pressure of 0.25 MPa, and autoclaved at a temperature of 50°C and a pressure of 5 atmospheres for 20 minutes to prepare a test specimen.
[0132] To measure the heat rework resistance, the test piece prepared above was left in an oven at 80°C for 10 hours, then removed and stored at room temperature for 120 hours, after which the adhesive layer was peeled off at a speed of 1.3 cm / sec.
[0133] To measure the rework resistance under moist heat, the test piece prepared above was left in an oven at 60°C and 90% RH for 12 hours, then stored at room temperature for 120 hours, and the adhesive layer was peeled off at a speed of 1.3 cm / sec. The evaluation criteria are as follows:
[0134] <Evaluation criteria> ◯: In both heat-resistant reworkability and moist heat-resistant reworkability, no adhesive remained on the glass substrate, and the base film (TAC film) was peeled off cleanly without tearing. ×: In one or more of the heat resistance reworkability and the moist heat resistance reworkability, the adhesive remains on the glass substrate, or the base film (TAC film) breaks during peeling.
[0135] (3) Evaluation of durability (heat resistance, moisture and heat resistance) The produced adhesive sheet was cut to a length of 200 mm and a width of 300 mm, and the release film was peeled off. The exposed adhesive layer was then attached to a glass substrate (210 mm x 350 mm x 0.7 mm) and autoclaved (50°C x 30 minutes, 0.5 MPa) to prepare a test specimen. The applied pressure was 5 kg / cm. 2 The work was carried out in a clean room to prevent the formation of air bubbles or foreign matter.
[0136] Heat resistance was evaluated by leaving the test piece at 80°C for 1000 hours and then observing whether or not bubbles or peeling occurred. Moisture heat resistance was evaluated by leaving the test piece at 60°C and 90% RH for 1000 hours and then observing whether or not bubbles or peeling occurred. At this time, the test piece was left at room temperature for 24 hours and then observed immediately before evaluating its condition. The evaluation criteria are as follows.
[0137] <Evaluation criteria> ◎: No bubbles or peeling ○: Air bubbles or peeling <5 pieces △: 5 pieces or less bubbles or peeling < 10 pieces ×: 10 or less bubbles or peeling
[0138] (4) Adhesion measurement The adhesive sheet produced above was cut into a size of 25 mm long x 50 mm wide, and the TAC film surface was attached to a SUS304 plate via double-sided adhesive tape (width: 25 mm, manufactured by SOOKWANG Co., Ltd.). The adhesive layer surface was then moved back and forth 20 times in the length direction (25 mm) using elastic rubber (neoprene rubber, manufactured by Goda Co., Ltd.) at a pressure of 1 MPa and a speed of 0.1 m / s. The distance the adhesive layer was pushed out on the TAC film was measured to determine the adhesion. The evaluation criteria are as follows.
[0139] ◎: Less than 10mm ○: 10mm or more and less than 15mm △: 15mm or more and less than 20mm ×: 20mm or more
[0140] (5) Evaluation of gel fraction Approximately 0.25 g of the adhesive layer of the adhesive sheet was attached to a 250 mesh wire net (100 mm x 100 mm) and surrounded to prevent the gel powder from leaking. After measuring the weight (B) with a precision balance, the wire net was immersed in an ethyl acetate solution for 3 days. The immersed wire net was taken out, washed with a small amount of ethyl acetate solution, and dried at 120°C for 24 hours, after which the weight (C) was measured. The gel fraction was calculated using the measured weight according to the following formula 1.
[0141] [Formula 1] Gel fraction (%) = (CA) / (BA) x 100
[0142] In the formula, A is the weight of the wire mesh, B is the weight of the wire mesh with the adhesive layer attached, and C is the weight of the wire mesh dried after immersion. Therefore, (BA) means the initial weight of the adhesive layer, and (CA) means the weight of the gelled adhesive layer.
[0143] The evaluation results are summarized in Table 2 below.
[0144] The adhesive strength ratio in Table 2 below means the ratio of adhesive strength at elevated temperature to adhesive strength at room temperature.
[0145] [Table 2] JPEG2025504304000012.jpg58155
[0146] The pressure-sensitive adhesive sheets according to the above-mentioned embodiments can realize improved reworkability even after being left for a long time while ensuring adhesion to the base film. Therefore, it can be confirmed that durability such as heat resistance and moist heat resistance is improved when the organosilicon compound contains a malonyl group or an acetoacetyl group and an amine group or a sulfide group. In contrast, it can be confirmed that the pressure-sensitive adhesive sheets according to the comparative examples have significantly reduced reworkability after being left for a long time in a high temperature and high humidity environment because the organosilicon compound does not have a malonyl group or an acetoacetyl group.
Claims
1. An acrylic copolymer; A non-yellowing type isocyanate-based or aziridine-based crosslinking agent; and an organosilicon compound having at least two carbonyl groups.
2. The pressure-sensitive adhesive composition according to claim 1 , wherein the acrylic copolymer is formed from a polymerizable mixture containing a (meth)acrylate monomer and a (meth)acrylic acid monomer.
3. The pressure-sensitive adhesive composition according to claim 2 , wherein the polymerizable mixture further comprises a polar functional group-containing crosslinkable monomer.
4. The pressure-sensitive adhesive composition according to claim 3 , wherein the polar functional group of the polar functional group-containing crosslinkable monomer includes at least one of a hydroxy group, an amide group, and an amine group.
5. The pressure-sensitive adhesive composition according to claim 3, wherein the content of the polar functional group-containing crosslinkable monomer is 0.1% by weight to 5% by weight based on the total weight of the polymerizable mixture.
6. The pressure-sensitive adhesive composition according to claim 2, wherein the (meth)acrylate monomer comprises a first monomer which is an alkyl (meth)acrylate monomer having 1 to 3 carbon atoms, and a second monomer which is an alkyl (meth)acrylate monomer having 4 to 12 carbon atoms.
7. The pressure-sensitive adhesive composition according to claim 6, wherein the content of the first monomer is 10% by weight to 40% by weight based on the total weight of the polymerizable mixture.
8. The pressure-sensitive adhesive composition according to claim 2, wherein the content of the (meth)acrylic acid monomer is 0.01% by weight to 1% by weight based on the total weight of the polymerizable mixture.
9. The pressure-sensitive adhesive composition according to claim 1 , wherein the organosilicon compound contains a nitrogen atom or a sulfur atom.
10. The pressure-sensitive adhesive composition according to claim 9 , wherein the organosilicon compound contains an amine group or a sulfide group.
11. The pressure-sensitive adhesive composition according to claim 1 , wherein the organosilicon compound has two carbonyl groups linked by a methylene group.
12. The pressure-sensitive adhesive composition according to claim 11 , wherein the organosilicon compound has a malonyl group or an acetoacetyl group.
13. The pressure-sensitive adhesive composition according to claim 1 , wherein the organosilicon compound comprises a compound represented by the following Chemical Formula 1 or the following Chemical Formula 2: 【Chemistry 1】 【Chemistry 2】 (In the above Chemical Formula 1 and the above Chemical Formula 2, R 1 is an alkoxy group having 1 to 12 carbon atoms, R 6 is an alkyl group having 1 to 12 carbon atoms or an alkoxy group having 1 to 12 carbon atoms, R 2 and R 7 each independently represents a divalent aliphatic hydrocarbon having 1 to 30 carbon atoms, R 3 ~R 5 and R 8 ~R 10 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an alkenyl group having 2 to 12 carbon atoms, an alkynyl group having 2 to 12 carbon atoms, or an alkoxy group having 1 to 12 carbon atoms.
14. The pressure-sensitive adhesive composition according to claim 1, comprising 0.1 to 3 parts by weight of the non-yellowing type isocyanate-based or aziridine-based crosslinking agent and 0.01 to 3 parts by weight of the organosilicon compound, relative to 100 parts by weight of the acrylic copolymer.
15. The pressure-sensitive adhesive composition according to claim 1 , further comprising an ionic antistatic agent.
16. A base film; A pressure-sensitive adhesive sheet comprising: a pressure-sensitive adhesive layer disposed on the base film and formed using the pressure-sensitive adhesive composition according to claim 1.
17. The pressure-sensitive adhesive sheet according to claim 16, wherein the pressure-sensitive adhesive sheet has an adhesive strength change rate of 0.8 to 2.2 according to the following formula 2: [Formula 2] Adhesion change rate = P H / P C (In formula 2, P C is the adhesive strength measured by attaching the adhesive sheet to an object, leaving it under conditions of a temperature of 23° C. and a relative humidity of 50% for 24 hours, and then peeling the adhesive sheet from the object at a peel speed of 300 mm / min and a peel angle of 180°, P H is the adhesive strength measured by attaching the pressure-sensitive adhesive sheet to the object, leaving it for 48 hours under conditions of a temperature of 50° C. and a relative humidity of 50%, and then peeling the pressure-sensitive adhesive sheet from the object at a peel speed of 300 mm / min and a peel angle of 180° under conditions of a temperature of 23° C. and a relative humidity of 50%.
18. A base film; A pressure-sensitive adhesive layer disposed on an upper surface of the base film and formed using the pressure-sensitive adhesive composition according to claim 1; and an anti-reflection layer disposed on the lower surface of the substrate film.
19. An image display device comprising the optical film according to claim 18.
Citation Information
Patent Citations
Liquid crystal element and pressure-sensitive adhesive composition therefor
JP1996104855A
Pressure-sensitive adhesive composition for optical films, pressure-sensitive adhesive optical film and image display
JP2009215528A
Organosilicon compound, method for producing the same, self-adhesive composition containing the same, self-adhesive polarizing plate, and liquid crystal display device
JP2011074080A
Adhesive composition
JP2014514387A
Tackifier composition and polarizing plate including the same
JP2015048481A